Foreign policy as public policy?: promises and pitfalls - Brummer, Klaus; Harnisch, Sebastian; Oppermann, Kai; Panke, Diana (Manchester University Press, 2019)
This book examines how foreign policy analysis can be enriched by 'domestic realm' public policy approaches, concepts and theories. Starting out from the observation that foreign policy has in many ways become more similar to (and intertwined with) 'domestic' public policies, it bridges the divide that still persists between the two fields. The book includes chapters by leading experts in their fields on arguably the most important public policy approaches, including, for example, multiple streams, advocacy coalition, punctuated equilibrium and veto player approaches. The chapters explore how the approaches can be adapted and transferred to the study of foreign policy and point to the challenges this entails. By establishing a critical dialogue between approaches in public policy and research on foreign policy, the main contribution of the book is to broaden the available theoretical 'toolkit' in foreign policy analysis.